Stochastic Mathematical Model for Food Waste Reduction in a Two-Level Supply Chain for Highly Perishable Products - Po-ngarm Somkun (International Journal of Supply Chain Management, 2017)
This article introduces a stochastic mathematical model for food waste reduction. Both consumers and retailers food supply chains are considered. The model describes consumer demand and consumption patterns, as well as retailers inventory replenishment policies, and considers the amount of food waste at each level. Primary data was collected by questionnaires to gain descriptive statistics about food waste in a particular area in Thailand. We also calculated the probability distribution of the coefficients of consumers consumption and buying behaviours to be used as our model input, using a statistics program. The mathematical relationships between the entities were simulated on a spreadsheet. A specific inventory replenishment policy was applied to the system, and assuming the lifetime of the products to be one day; i.e. highly perishable products only. The results show that the size of the unit sales has an impact on the total food waste produced by the supply chains. The best unit size of a sale can be properly determined using the model in order to lessen food waste problems.